No recovery: long-term monitoring reveals low and fluctuating populations of the endemic reef-building vermetid snail Dendropoma anguliferum on Levantine shores - RILOV, GIL; ZILBERMAN, SHAI; RAANAN, GUY; SONEGO, YUVAL (Mediterranean Marine Science, 2026)
Dendropoma anguliferum is an endemic reef-building vermetid gastropod of the southeastern Mediterranean that has historically been considered a key ecosystem engineer. In studies from the past decade and a half, this gastropod has been shown to have very low abundance compared to past anecdotal data. A recent study, based on a single survey at a single site, claims that there are signs of recovery of this species on the Israeli coast. Our study analyzed 16 years of seasonal monitoring data from four rocky shore sites to assess long-term population trends along this coast. Results show that D. anguliferum maintains a persistently low average cover (0 1.5%) at the seaward edge of the platform, with many temporal fluctuations, indicating no sustained recoveries. A comparative analysis with this recent short-term survey in a region similar to one of the monitoring sites yielded comparable abundance estimates, validating both methodologies for assessing the abundance of this sessile, aggregative, species. In contrast, the co-occurring vermetid, Vermetus triquetrus, exhibited much higher cover at some sites and strong fluctuations. This study emphasizes the value of persistent ecological monitoring over one-off snapshot surveys for evaluating species trajectories and developing conservation strategies. These findings also underscore the need for coordinated, continuous, Mediterranean-wide efforts using standardized protocols and advocates for the use of advanced technologies to assess the long-term status of vermetid reefs at the basin scale, especially in the face of increasing pressure due to climate change and other stressors.